2020
DOI: 10.3390/v12020205
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of AbTJ, an Acinetobacter baumannii Phage, and Functional Identification of Its Receptor-Binding Modules

Abstract: A. baumannii is an opportunistic pathogen and a major cause of various community-acquired infections. Strains of this species can be resistant to multiple antimicrobial agents, leaving limited therapeutic options, also lacking in methods for accurate and prompt diagnosis. In this context, AbTJ, a novel phage that infects A. baumannii MDR-TJ, was isolated and characterized, together with its two tail fiber proteins. Morphological analysis revealed that it belongs to Podoviridae family. Its host range, growth ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
0
6
1
Order By: Relevance
“…Phage vABWU2101 could adsorb into host cells rapidly. Previous studies on Podoviridae and Autographiviridae phages showed a latency period of 15-90 min and burst size of 70-300 particles per infected cell [58,59]. Phage vABWU2101 had a short latency period and a large burst size when compared with these earlier reports.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Phage vABWU2101 could adsorb into host cells rapidly. Previous studies on Podoviridae and Autographiviridae phages showed a latency period of 15-90 min and burst size of 70-300 particles per infected cell [58,59]. Phage vABWU2101 had a short latency period and a large burst size when compared with these earlier reports.…”
Section: Discussioncontrasting
confidence: 45%
“…However, the phage classification was confirmed by genomic analysis. Several Podoviridae or Autographiviridae phages specific for A. baumannii have been studied, such as phage SH-Ab 15497 [57], phage AbTJ [58], phage vB_AbaP_AS11, phage vB_AbaP_AS12 [59], and phage Aristophane [60]. Based on the spot test and the EOP analysis, phage vABWU2101 was found to be specific for A. baumannii strains and had a narrow host range activity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, even when phage tails have similar morphologies, it is unusual that they recognize similar targets, explaining the high specificity observed in phage-host recognition systems (27). In this sense, RBPs can be exploited, for example, as tools for bacterial diagnostics (29)(30)(31)(32)(33).…”
mentioning
confidence: 99%
“…These phages include AP22 (gp54), APK32 (gp46), APK48 (gp43), P1 (gp43), B9 (gp69), and TaPaz (gp79) (Oliveira et al, 2017 , 2018 ; Knirel et al, 2020 ; Popova et al, 2020a ; Shchurova et al, 2021 ). Furthermore, halo formation was detailed in the following phages but the protein responsible was not confirmed: AbTj (gp53) and WCHABP1 (gp5) (Zhou et al, 2018 ; Xu et al, 2020 ; Drobiazko et al, 2022 ). All the eight abovementioned proteins were modeled as homotrimers with AlphaFold Multimer and showed narrow midsections and larger globular regions ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%